Clinical Performance of Two Types of Primary Molar Indirect Crowns Fabricated by 3D Printer and CAD/CAM for Rehabilitation of Large Carious Primary Molars - Al-Halabi, Mohammed Nour; Bshara, Nada; Nassar, Jihad Abou; Comisi, John C.; Rizk, Charline K. (European Journal of Dentistry, 2021)
Objectives This randomized clinical trial aimed to evaluate clinical outcomes of two types of esthetic crowns fabricated using a three-dimensional (3D) dental printer and computer-aided design and manufacturing (CAD/CAM) system as an alternative full-coronal restoration for extensively carious pulp-treated primary molars.Materials and Methods Randomization was done for 50 lower primary molars in 50 child patients, split into two groups based on the fabrication method used: Group A: CAD/CAM crowns using polymethyl methacrylate (PMMA) blocks and Group B: 3D dental printed crowns using GC photopolymer resin. All crowns were evaluated at baseline and at 3rd, 6th, and 12th months using the U.S. Public Health Service criteria for gingival health, retention, and marginal integrity for both groups.Statistical Analysis The survival rate of 3D-printable crowns was 84% compared with 80% survival rate using CAD/CAM fabricated crowns at the end of the 12th-month follow-up. No statistically significant differences were noted in restoration failure. In the evaluation of gingival health between the two groups’ follow-up times, no statistically significant differences were noted at the 3rd- and 6th-month follow-ups, yet at the 12th month, statistically significant differences were noted (p = 0.022) when comparing gingival health. No statistically significant differences were noted between the two groups when comparing marginal integrity scores in all the follow-up periods.Conclusion Resin crowns fabricated via 3D dental printer and PMMA crowns fabricated using CAD/CAM are acceptable esthetic choices in restoring pulp-treated primary molars with great marginal integrity and crowns retention. 3D-printed resin crowns showed less cementing failure and performed better regarding gingival response compared with PMMA crowns.
Keywords: 3D dental printer; CAD/CAM; posterior; crowns; primary teeth